Ireland's peculiar microfinance revolution, c. 1836-1845 - Eoin McLaughlin; Rowena Pecchenino (The European Association for Banking and Financial History (EABH), 2019)
In the decade before the famine, Ireland experienced a boom in Microfinance Institutions (MFIs). This paper analyses the motivations of MFI proponents and practitioners, and finds evidence linking the boom in MFIs with the introduction of the poor law in 1838. Many contemporary writers saw microfinance as a complex tax avoidance/reduction scheme that could lessen the burden on rate payers by helping the poor help themselves. The link between MFIs and the poor law is confirmed by an econometric analysis of MFIs at the level of the poor law union.
Keywords: G21; H75; I38; N23; N33; N83; 330; microfinance; inequality; development; Ireland